Knowledge, Attitude and Practice of Staff nurses on Hospital Acquired Infections in tertiary care Hospital of Dhaka city - Kabir, ASM Anwarul; Akhter, Farjana; Sharmin, Mahbuba; Akhter, Khaleda; Begum, Mosammat Beauty; Saha, Arup Kumar; Ahmed, Imtiaz (Northern International Medical College Journal, 2018)
Introduction : Hospital acquired Infections (HAIs) are called those infections that were not present at the time of patient’ hospitalization in a hospital and have been acquired after hospitalization. Nurses are an important part of the any healthcare team who play a unique role in the control of Hospital acquired infections. Objective : The aim of this study was to investigate the level of knowledge, attitudes, and practices of staff nurses about preventing the spread of hospital acquired infections (HAIs) at tertiary care Hospital of Dhaka city. Methods and Materials : This descriptive cross-sectional study was done among nurses having two years experience from two tertiary level hospitals in Dhaka city during January to June 2017. Self administered questionnaire containing different set of questions regarding knowledge, attitude and practice on HAI were used as a tool for data collection. Questionnaire was supplied to all staff nurses available at different in-patient wards of these two hospitals. Only 234 staff nurses who completed and returned the questionnaire were included in this study. Data were analyzed using Microsoft excel 2013 software. Result : Staff nurses were found to have good knowledge, moderately positive attitude but poor practice in prevention of hospital acquired infections. About 95% of the participants considered that prevention of HAIs were a valuable part of their role. About 65% of the staff nurses had received formal training regarding hand hygiene. The 100 % of participants felt that they would be less likely to transmit infection to the patients if they performed hand-hygiene. About 64% of them argued that hand hygiene agents were not readily available in current settings. Regarding practice, only 6% performed hand hygiene before patients contact and 27% of the staff nurses reported that they often forgot to perform hand hygiene. Conclusion : The finding of this study revealed a good knowledge of infection prevention among the majority of participants with relatively minimal level of practice. For strengthening the knowledge, attitude and practice towards HAIs, there is in need of developing regular training program and monitoring on performance feedback regarding hand hygiene is recommended. Northern International Medical College Journal Vol.10(1) Jul 2018: 347-350